Usury and Bank Interest in the View of Neo Revivalists and Modernists - Nurjannah Nurjannah; Muslimin Kara; Rahman Ambo Masse; M Afief Mubayyin (Institut Agama Islam Negeri Padngsidimpuan, 2023)
Al-Maududi and Abdullah Saeed are Muslim scholars. He contributed various thoughts in the field of economics, one of which is related to usury and bank interest. But there are differences of opinion between the two. The purpose of this study is to look at the views of Al-Maududi and Abdullah Saeed regarding usury and bank interest. The method used is a literature study with a descriptive qualitative approach. Data sources come from secondary data sources, namely journals and books related to the discussion. The result of the research is that Al-Maududi firmly rejects bank interest because the institution is a source of danger and evil through its influence on human character because it is influenced by the love of money. In addition, Al-Maududi stated that there is an element of injustice in bank interest and it is clearly prohibited in Islam. While Abdullah Saeed views the prohibition of usury based on the historical situation and conditions behind the revelation of the verse, so related to bank interest Abdullah Saeed argues that bank interest is not included in usury because the context of usury in ancient times is very much different from usury today.